1951
DOI: 10.1021/ja01155a057
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Studies of Oxidation—Reduction Polymerization and Molecular Weight of “Teflon” Tetrafluoroethylene Resin

Abstract: overnight. After washing with water and drying, the crude product was distilled, yielding 19.4 g. (33%) of X a t 240-242' and 0.05 mm., n% 1.4318.Anal. Calcd. for C~oH~~o0~~Sia: Si, 9.58; MRD, 325.3; mol. wt., 1172. Found: Si, 9.84, 10.01; MRD, 321.7; mol. wt., 1143. Heptakis-( 1,3-dimethylbutoxy)-trisiloxanol (XI) .-Eightyfive grams (0.143 mole) of the disiloxanol (IX) was added dropwise with stirring to a cold mixture of 42 g.(0.140 mole) of IT and 30 g. of dry pyridine. After an hour 70 ml. of water w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1954
1954
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…The iron/bisulfite/persulfate initator system was used because at low temperatures the reaction rate of persulfate-bisulfite initiators with TFE emulsion copolymerizations is quite slow [47]. Berry reported that the reaction between persulfate and bisulfite was found to have a threshold initiation temperature for tetrafluoroethylene of 35-36 8C, while the bisulfite/iron initiator had a threshold initiation temperature for TFE of 0-10 8C [48]. The source of iron in our polymerizations was from the buffer salts as well as the 316 ss autoclave.…”
Section: Copolymerizationmentioning
confidence: 99%
“…The iron/bisulfite/persulfate initator system was used because at low temperatures the reaction rate of persulfate-bisulfite initiators with TFE emulsion copolymerizations is quite slow [47]. Berry reported that the reaction between persulfate and bisulfite was found to have a threshold initiation temperature for tetrafluoroethylene of 35-36 8C, while the bisulfite/iron initiator had a threshold initiation temperature for TFE of 0-10 8C [48]. The source of iron in our polymerizations was from the buffer salts as well as the 316 ss autoclave.…”
Section: Copolymerizationmentioning
confidence: 99%
“…Alkenyl fluorides have utility as monomers for free-radical polymerization to form fluorinated polymers (e.g., Teflon) [184,185], and as peptide mimics due to the similarity in size and dipole moment between amide bonds and fluoroalkene groups [186][187][188][189][190]. While fluoroalkene synthesis is often accomplished using Wittig-type reactions [191][192][193][194][195], several examples have been reported using gold catalysis and alkyne substrates.…”
Section: Alkenyl Fluoride Synthesismentioning
confidence: 99%
“…Polyethylene decomposes appreciably, 0.16 percent p CI' minute at 385 0 C; poly tetrafluoro ethylene decomposes at the same rate at 489 0 0, only 104 deg higher [9,25]. For comparison, bond-dissociation energies in related simple molecules are: for C2H 6 and other lower paraffin , C-C = 80 kcal, C-H = 101 kcal ; for C2F 6 , C-C = 124 kcal, C-F = 107 kcal. All figures except C-F arc derived from electron-impact data.…”
Section: 1 General Considerationsmentioning
confidence: 98%
“…Berry and Peterson [6] polymerized tetrafluoroethylene in the presence of radioactive sulfur compounds to secure an estimate of the molecular weight of th e polymer. The molecular weight of poly tetrafluoroethylene has never been measured directly, because no solvent for this polymer is lmown.…”
Section: Polymerization Of Tetra£luoroethylenementioning
confidence: 99%